2015
DOI: 10.5336/medsci.2014-41225
|View full text |Cite
|
Sign up to set email alerts
|

Reversal Effects of Sugammadex in Diabetic Patients Having Neuromuscular Block with Rocuronium

Abstract: A AB BS S T TR RA AC CT T O Ob bj je ec ct ti iv ve e: : In our study we aimed to compare the time of antagonism and effect of sugammadex which is used for antagonism of rocuronium on diabetic and nondiabetic patients. Sugammadex is a new generation antagonist of neuromuscular blockade which effects by encapsulating rocuronium molecules in the neuromuscular junction through acting like a synthetic receptor of rocuronium. M Ma at te er ri ia al l a an nd d M Me et th ho od ds s: : Included patients were divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In our previous study to compare the time of antagonism and effect of sugammadex (2 mg/kg) which is used for antagonism of rocuronium 0.6 mg/kg on diabetic (n=21) and nondiabetic patients (n=20), we found that extubation time (time from sugammadex administration to TOF ratio reaching 0.9) was 434.6 ± 857. 1 [205 (67-4120)] s in diabetics and 250.4 ± 108.4 [247 (106-462)] seconds in nondiabetics (P = 0.948) [19].…”
Section: Discussionmentioning
confidence: 98%
“…In our previous study to compare the time of antagonism and effect of sugammadex (2 mg/kg) which is used for antagonism of rocuronium 0.6 mg/kg on diabetic (n=21) and nondiabetic patients (n=20), we found that extubation time (time from sugammadex administration to TOF ratio reaching 0.9) was 434.6 ± 857. 1 [205 (67-4120)] s in diabetics and 250.4 ± 108.4 [247 (106-462)] seconds in nondiabetics (P = 0.948) [19].…”
Section: Discussionmentioning
confidence: 98%